Pengaruh Target Kerja dan Stres Kerja terhadap Kepuasan Kerja Karyawan PT. BTPN Syariah Kantor Cabang Cikampek - Silvia Audina; Junengsih; Partimah (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of work targets and work stress on employee job satisfaction at BTPN Syariah, Cikampek Branch Office. The research is driven by increasing performance pressure, rising workload, and growing stress levels that potentially reduce job satisfaction and increase turnover intention. The theoretical review highlights the interrelationship among work targets, work stress, and job satisfaction through psychological mechanisms, task demands, and perceptions of fairness. A quantitative approach was employed using structured questionnaires distributed to all 30 employees through a saturated sampling technique. The research instruments were tested using validity, reliability, and classical assumption tests. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. The findings reveal that both work targets and work stress have significant effects on job satisfaction, either partially or simultaneously. Work targets contribute to employees’ sense of achievement and psychological well-being, while high work stress significantly decreases job satisfaction. Simultaneously, both variables explain a meaningful proportion of the variation in job satisfaction. These results offer practical implications for BTPN Syariah’s management, particularly in designing realistic performance targets and implementing effective stress management strategies to improve employee well-being and organizational performance.